2015
DOI: 10.1007/s11743-014-1653-7
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Boron Compounds for Stabilization of Lipase from Pseudomonas aeruginosa ES3 for the Detergent Industry

Abstract: This study aimed to characterize a lipase that is highly active and stable under typical washing conditions for use as a detergent ingredient by investigating the effects of various boron compounds on lipase stabilization under different conditions. In addition, the antimicrobial activity of the boron compounds used in enzyme stabilization was examined in order to obtain an effective antimicrobial detergent. A lipase-producing bacterium was isolated from kitchen wastewater samples using Rhodamine-B Agar medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…2). The lipase maintains its activity from 30 to 50 C with the optimum temperature at around 40 C. When the temperature stability profile was taken into account, it was observed that the activity of the lipase remained more than 80% at 30, 40, and 50 C. When the optimum temperature of the studied lipase is considered, it has been observed that it is similar to the lipases previously recommended as the detergent ingredients (Boran & Ugur, 2016;Hasan et al, 2010;Sarac, Ugur, Boran, & Elgin, 2015;Saraswat, Verma, Sistla, & Bhushan, 2017). In addition, maximum activities were previously reported for extracellular lipases from Streptomyces sp.…”
Section: Effects Of Temperaturementioning
confidence: 64%
See 3 more Smart Citations
“…2). The lipase maintains its activity from 30 to 50 C with the optimum temperature at around 40 C. When the temperature stability profile was taken into account, it was observed that the activity of the lipase remained more than 80% at 30, 40, and 50 C. When the optimum temperature of the studied lipase is considered, it has been observed that it is similar to the lipases previously recommended as the detergent ingredients (Boran & Ugur, 2016;Hasan et al, 2010;Sarac, Ugur, Boran, & Elgin, 2015;Saraswat, Verma, Sistla, & Bhushan, 2017). In addition, maximum activities were previously reported for extracellular lipases from Streptomyces sp.…”
Section: Effects Of Temperaturementioning
confidence: 64%
“…In a study, more than 86% of the enzyme activity was detected in the existence of Ariel after 1 h incubation (Rajanikanth & Damodharam, ). In another study, Lipolase® and P. aeruginosa ES3 lipase retained 100% of their activities against Omo, Ariel, and Pril (Sarac et al, ). In the presence of Omo and Pril, the B. multivorans SB6 lipase retained 40.6% and 100% of its activity, respectively (Boran & Ugur, ).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Lipase-produced bacterial isolates were collected from kitchen wastewater samples using Rhodamine B agar medium [14], and their stability towards detergent was previously determined [15] using Rhodamine B agar medium containing a commercial detergent [16]. Lipase activity of isolates was assessed by inoculating nutrient broth (NB) with 2 % inoculum from an overnight culture that was then incubated for 24 h at 30°C and 130 rpm.…”
Section: Isolation Of Lipolytic Microorganisms and Culture Conditionsmentioning
confidence: 99%